The socio-cultural sustainability of livestock farming: an inquiry into social perceptions of dairy farming - Boogaard, Birgit K.; Oosting, Simon J.; Bock, B.B.; Wiskerke, J.S.C. (Elsevier, 2011)
Over the past 50 years, the scale and intensity of livestock farming have increased significantly. At the same time, Western societies have become more urbanised and fewer people have close relatives involved in farming. As a result, most citizens have little knowledge or direct experience of what farming entails. In addition, more people are expressing concerns over issues such as farm animal welfare. This has led to increasing public demand for more sustainable ways of livestock farming. To date, little research has been carried out on the social pillar of sustainable livestock farming. The aim of this study is to provide insights into the sociocultural sustainability of livestock farming systems. This study reviews the key findings of earlier published interdisciplinary research about the social perceptions of dairy farming in the Netherlands and Norway (Boogaard et al., 2006, 2008, 2010a and 2010b) and synthesises the implications for sociocultural sustainability of livestock farming. This study argues that the (sociocultural) sustainable development of livestock farming is not an objective concept, but that it is socially and culturally constructed by people in specific contexts. It explains the social pillar of the economics/ecological/social model sustainability in terms of the fields of tensions that exist between modernity, traditions and naturality – ‘the MTN knot’ – each of which has positive and negative faces. All three angles of vision can be seen in people's attitudes to dairy farming, but the weight given to each differs between individuals and cultures. Hence, sociocultural sustainability is context dependent and needs to be evaluated according to its local meaning. Moreover, sociocultural sustainability is about people's perceptions of livestock farming. Lay people might perceive livestock farming differently and ascribe different meanings to it than experts do, but their ‘reality’ is just as real. Finally, this study calls for an ongoing collaboration between social and animal scientists in order to develop livestock farming systems that are more socioculturally sustainable.